REDEFINISI HUKUM ISLAM DALAM KERANGKA DEMOKRASI Eksperimentasi Muḥammad Shaḥrūr - Muhyar Fanani (Al-Ahkam, 2014)
This article discusses the new paradigm of Islamic law which is offered by Muḥammad Shaḥrūr, one of the contemporary Muslim thinkers from Suria. The focus of study on this paper is an attempt to criticize the redefinition of the basic concepts of Islamic law in Shaḥrūr view. According to Shaḥrūr, redefinition basic concepts in Islamic law must be done as a starting point to develop a new paradigm of Islamic law which is based on anthropocentric approaches, —not theocentric approaches. Islamic law is civil law, democratic and positive. Therefore, it requires more realistic, elastic, and implementable definition. For Shaḥrūr, the existence of a new paradigm, such as the democratization of Islamic law is very urgent in the midest of the Muslim world today on the era of the nation state, constitutionalism and democracy, rapidly changing, and increasingly distant from the tyranny period